Eucalypt plantations for forest restoration in a fire-prone mosaic of grasslands and forests in northern Argentina - Montiel, M. Rosario (2021)
In ecosystems with grassland-forest boundaries, tree plantations could be used to promote forest restoration. In the Humid Chaco region of central South America, fire is one of the main disturbances that shapes the landscape. As eucalypt plantations are flammable, the contribution they can make to forest restoration is questionable. We planted saplings of five native tree species in three different environments (Forests, Grasslands, and Eucalypt plantations) and assessed microclimatic conditions likely to influence sapling survival and growth. After 1 year, accidental fires that affected much of the study area allowed us to investigate the susceptibility of different environments to fire occurrence and post-fire sapling survival. We planted 600 saplings in four plots per environment. We evaluated fire occurrence in the study area for 2 years and ask whether this factor affects sapling survival. In Grasslands, microclimatic conditions were more extreme than in Plantations. Plantations and Forests showed high pre-fire sapling survival but growth was almost double in Plantations, similar to Grasslands for most species. In the study area, fire frequency was similar in Plantations and Grasslands, while Forests plots never burnt during the two year study period. Fire reduced sapling survival in Plantations, but not in Grasslands where survival was low and similar in burned and unburned plots. For top-killed plants, post-fire resprouting ability was species-specific. While more firm conclusions await future studies with even larger sample sizes, our results indicate that fire management may be necessary in order to use eucalypt plantations as nurses in this fire-prone ecosystem.